Effectiveness and safety of finerenone in diabetic kidney disease patients: a real-world observational study from China - Jingying Zhou; Le Kang; Chenjie Gu; Xinwei Li; Xianan Guo; Ming Fang (Renal Failure)
Aims Finerenone has been approved for treating diabetic kidney disease (DKD) with reducing cardiorenal risk. Real-world data on finerenone treatment for the management of DKD are presently lacking. This study aimed to investigate the effect of finerenone on the renal parameters of the Chinese DKD population in the real-world medical setting for the first time, especially in combination with renin–angiotensin system inhibitors (RASi) and sodium-glucose cotransporter 2 inhibitors (SGLT2i).Methods Forty-two DKD patients were selected and completed a 6-month finerenone treatment. Renal parameters and adverse effects were collected at every visit.Results The median urine albumin-to-creatinine ratio (UACR) was 1426.11 (755.42, 3638.23) mg/g. Among them, the proportion of patients with a UACR of 300–5000 mg/g was 76.2%, and the proportion of patients with a UACR of >5000 mg/g was 14.3%. The median estimated glomerular filtration rate (eGFR) was 54.50 (34.16, 81.73) mL/min/1.73 m2. Finerenone decreased the UACR significantly throughout the study period (p < .05). The maximal decline of UACR at month 6 was 73%. Moreover, the proportion of patients with a 30% or greater reduction in UACR was 68.42% in month 6. There was a smaller decline (9–11%) in the eGFR after initiating finerenone (p > .05). One patient each discontinued finerenone due to hyperkalemia (2.4%) and acute kidney injury (2.4%). No patient reported hypotension, breast pain, and gynecomastia.Conclusions This study from China first demonstrated finerenone decreased UACR with manageable safety in real-world DKD treatment. A triple regimen of RASi, SGLT2i, and finerenone may be a promising treatment strategy for lowering albuminuria and reducing hyperkalemia risk in advanced DKD patients.